LEGAL ASPECTS OF HOUSEHOLD WASTE MANAGEMENT IN KAZAKHSTAN AND FOREIGN COUNTRIES: COMPARATIVE LEGAL ANALYSIS - Nukusheva, Айгуль Ашимовна; Aitimov, Болат Жолдасбекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
Management of household waste is an important task for all countries of the world in order to achieve environmental equilibrium, sustainable development and climate change. At the moment, the issue of managing household waste for Kazakhstan has a special relevance. The scientific and practical analysis of the management of household waste in Kazakhstan, its features and characteristics was conducted in this article. The purpose of the study is to assess the state of solid household waste management in Kazakhstan, to conduct a comparative legal analysis of Kazakh legislation and legislation of foreign countries, as well as to analyze the prospects in solid household waste management in Kazakhstan for subsequent optimization of the mechanism of the modern legislative framework for household waste management in the Republic of Kazakhstan. On the basis of the outlined conclusions and foreign experience of management of household waste, the author proposed and substantiates the introduction of a single integrated approach to managing household waste in the Republic of Kazakhstan. The analysis showed that the legislation of the Republic of Kazakhstan in the relevant sector is today at the development stage and requires a single system integrating approach, as well as the practices for the application of legislation in the sphere of waste management in practice. Moreover, in the context of countering the deterioration of the environmental situation in the republic, it is of particular importance to the formation of ecological culture among citizens of Kazakhstan. The current situation with the policies of household waste management is an important factor in the rapid deterioration of the environmental situation in the country. Therefore, it is important to form a comprehensive information access system by electronic management, and organizing a holistic system of interaction between civil service, public sector and business.